Looking into the performance-based financing black box : Evidence from an impact evaluation in the health sector in Cameroon - de Walque, Damien (Oxford University Press, 2022)
Performance-based financing (PBF) is a complex health systems intervention aimed at improving the coverage and quality of care. Several studies have shown a positive impact of PBF on health service coverage, often coupled with improvements in quality, but relatively little is known about the mechanisms driving those results. This article presents results of a randomized impact evaluation in Cameroon designed to isolate the role of specific components of the PBF approach with four study groups: (i) PBF with explicit financial incentives linked to results, (ii) direct financing with additional resources available for health providers not linked to performance, (iii) enhanced supervision and monitoring without additional resources and (iv) a control group. Overall, results indicate that, when compared with the pure control group, PBF in Cameroon led to significant increases in utilization for several services (child and maternal vaccinations, use of modern family planning), but not for others like antenatal care visits and facility-based deliveries. In terms of quality, PBF increased the availability of inputs and equipment, qualified health workers, led to a reduction in formal and informal user fees but did not affect the content of care. However, for many positively impacted outcomes, the differences between the PBF group and the group receiving additional financing not linked to performance are not significant, suggesting that additional funding rather than the explicit incentives might be driving improvements. In contrast, the intervention group offering enhanced supervision, coaching and monitoring without additional funding did not experience significant impacts compared to the control group.